Characterization of the naïve kappa light chain murine immunoglobulin repertoire in spaceflight - Ward, Claire (Kansas State University, 2017)
Immunoglobulins are receptors expressed on the outside of a B cell that can specifically bind pathogens and toxic substances within a host. These receptors are heterodimers of two chains: heavy and light, which are encoded at separate loci. Enzymatic splicing of gene segments at heavy and light chain loci within the genomic DNA in every B cell results in a highly diversified and specific repertoire of immunoglobulins in a single host. Spaceflight is known to affect reduce splenic B cell populations and B cell progenitors within the bone marrow, potentially restricting the diversity of the immunoglobulin repertoire (Ig-Rep). The objective of this thesis project was to characterize the impact of spaceflight on the kappa light-chain Ig-Rep of the C57BL/6 mouse. High-throughput sequencing (HTS) technologies have enabled the rapid characterization of Ig-Reps, however, standard Ig-Rep workflows often rely the amplification of immunoglobulin sequences to ensure the capture immunoglobulin sequences from rare B cell clones. Additionally, the Ig-Rep is often assessed in sorted B cell populations. Opportunities for spaceflight experiments are limited and costly, and the exclusive amplification of immunoglobulin sequences prior to HTS results in a dataset that cannot be mined for additional information. Furthermore, due to the difficulties of tissue collection in spaceflight, HTS of sorted B cell populations is not feasible. We optimized a protocol in which the Ig-Rep was assessed from unamplified whole tissue immunoglobulin transcripts. The Ig-Rep was characterized by gene segment usage, gene segment combinations and the region in which gene segments are joined. HTS datasets of ground control animals and animals flown aboard the International Space Station were compared to explore the impact of spaceflight on the unimmunized murine Ig-Rep.
Keywords: Antibody repertoire; Immunoglobulin repertoire; High-throughput sequencing; Spaceflight